2017
DOI: 10.1111/ppa.12652
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of surface drip irrigation on Verticillium dahliae propagules differing in persistence in soil and on verticillium wilt of olive

Abstract: For efficient integrated management of verticillium wilt in olive (VWO), it is important to establish whether irrigation treatments (with Verticillium dahliae‐free water) that mitigate the disease in V. dahliae‐infested soil, also reduce the levels of more and less persistent propagules of the pathogen in the soil. Effects of irrigation on VWO and V. dahliae propagules were evaluated under natural environmental conditions. Potted plants were irrigated (pathogen‐free water) to two ranges of soil water content (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(55 citation statements)
references
References 28 publications
5
48
0
Order By: Relevance
“…The authors of that study (Gaudreault et al ., ) postulated that high soil water pressures may hasten potato early dying by slowing root growth and/or indirectly increasing the rate of microsclerotial germination. Previous findings in olive plants (Santos‐Rufo et al ., ) indicated that AUIPC ID , AUIPC SwD and AUIPC SdD were lower at HR than at LR, and that AUIPC MpD , which is partly related to the rate of microsclerotial germination, was not affected by RWC. Thus, because HR increases IIP but reduces relative below‐ground biomass and R wr , together with relative above‐ground biomass and AUGPC, it is suggested, in line with Gaudreault et al .…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The authors of that study (Gaudreault et al ., ) postulated that high soil water pressures may hasten potato early dying by slowing root growth and/or indirectly increasing the rate of microsclerotial germination. Previous findings in olive plants (Santos‐Rufo et al ., ) indicated that AUIPC ID , AUIPC SwD and AUIPC SdD were lower at HR than at LR, and that AUIPC MpD , which is partly related to the rate of microsclerotial germination, was not affected by RWC. Thus, because HR increases IIP but reduces relative below‐ground biomass and R wr , together with relative above‐ground biomass and AUGPC, it is suggested, in line with Gaudreault et al .…”
Section: Discussionmentioning
confidence: 92%
“…Stomatal conductance ( g s ) was not significantly affected by irrigation treatments or soil infestation before maximum values of the derivative function of the DI progress curves (d y /d t ) for all irrigation treatments were reached each year (23, 388 and 752 dpt), according to Santos‐Rufo et al . () (Table ). However, significant ( P < 0.05) average reductions in g s were observed (33.3%, 47.7% and 17.2%) in +V plants at approximately maximum time values of the d y /d t for all irrigation treatments for the three years under study (49, 433 and 794 dpt, respectively) (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations